Industrial-based competency and expertise assessment: study of management assessments at SMK center of excellence and vocational education and training (vet) - Vachruddin, Vrisko Putra; Susanto, Bambang Adi; Karim, Abdul Rahim; Kusaeri, Kusaeri; Aditomo, Anindito (Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
Vocational education must be able to establish a good working relationship with the world of business, industry, and work. Sustainable and mutually beneficial cooperative relationships between the industrial world and educational institutions must be connected simultaneously. To achieve this, industry-based competency and expertise assessment is needed by involving industry practitioners as an examination team. This study aims to deepen the management model of industry-based competency and expertise assessment in Vocational Education and Training (VET) and Center of Excellence Vocational Schools. The approach in this study uses a qualitative approach with field research methods conducted at SMK YPM 3 Taman and a literature review on research related to assessment in Vocational Education and Training (VET). The type of research uses the type of case study and text analysis. Data collection techniques used participant observation, unstructured interviews classified as in-depth interviews, and documentation review. Data analysis techniques used modified analytic induction techniques and Miles' interactive model data analysis techniques. While checking the validity of the data through credibility, dependability, confirmability, and transferability. The results of this study show that the apprenticeship scheme and the requirements for the implementation of competency and expertise assessment in vocational schools of expertise centers (SMK-PK) are divided into two assessments, namely: internal competency and expertise assessment with productive teacher assessors as examiners and external competency and expertise assessment with industry practitioners as examiners. Meanwhile, the management of industry-based competency and skills assessment in vocational education and training (VET) is based on competency-based training (CBT).